การบริหารการวัดและประเมินผลการศึกษากับการปฏิบัติงานตามภารกิจการวัดและประเมินผลการเรียนรู้ ของสถานศึกษาในจังหวัดนครปฐม สังกัดสำนักงานเขตพื้นที่การศึกษามัธยมศึกษา เขต 9 - ศรีสวัสดิ์, ทัศนีย์; เจนอักษร, นพดล (วารสารการบริหารการศึกษา มหาวิทยาลัยศิลปากร, 2016)
การวิจัยครั้งนื้ มีวัตถุประสงค์เพื่อทราบ 1)การบริหารการวัดและประเมินผลการศึกษา ของสถานศึกษาในจังหวัดนครปฐม สังกัดสำนักงานเขตพื้นที่การศึกษามัธยมศึกษา เขต 9 2) การปฏิบัติงานตามภารกิจการวัด และประเมินผลการเรียนรู้ของสถานศึกษา ในจังหวัดนครปฐม สังกัดสำนักงาน เขตพื้นที่การศึกษามัธยมศึกษา เขต 9 3) ความสัมพันธ์ระหว่างการบริหารการวัดและประเมินผลการศึกษากับการปฏิบัติงานตามภารกิจการวัดและประเมินผลการเรียนรู้ ของสถานศึกษาในจังหวัดนครปฐม สังกัดสำนักงานเขตพื้นที่การศึกษามัธยมศึกษา เขต 9 กลุ่มตัวอย่างคือ สถานศึกษาในจังหวัดนครปฐม สังกัดสำนักงานเขตพื้นที่การศึกษามัธยมศึกษา เขต 9 จำนวน 28 โรงเรียน ผู้ให้ข้อมูล ประกอบด้วย ผู้อำนวยการโรงเรียน รองผู้อำนวยการฝ่ายบริหารวิชาการหรือหัวหน้าฝ่ายบริหารงานวิชาการ หัวหน้ากลุ่มสาระการเรียนรู้ นายทะเบียน ครูวัดผลและครูผู้สอนรวมโรงเรียนละ 6 คน รวมทั้งสิ้น 168 คน เครื่องมือที่ใช้เป็นแบบสอบถามเกี่ยวกับการบริหารงานวัดและประเมินผลการศึกษาที่สร้างขึ้นตามแนวคิดของกมล ภู่ประเสริฐและคณะ และการปฏิบัติงานตามภารกิจการวัดและประเมินผลการเรียนรู้ ที่สร้างขึ้นตามแนวคิดของสำนักงานคณะกรรมการการศึกษาขั้นพื้นฐาน สถิติที่ใช้ในการวิจัย คือ ความถี่ ร้อยละ มัชฌิมเลขคณิตส่วนเบี่ยงเบนมาตรฐาน และการวิเคราะห์ค่าสัมประสิทธิ์สหสัมพันธ์ของเพียร์สัน ผลการวิจัยพบว่า 1.การบริหารการวัดและประเมินผลการศึกษาของสถานศึกษาในจังหวัดนครปฐม สังกัดสำนักงานเขตพื้นที่การศึกษา มัธยมศึกษา เขต 9 โดยภาพรวมและรายด้าน อยู่ในระดับมาก 2.การปฏิบัติงานตามภารกิจการวัดและประเมินผลการเรียนรู้ของสถานศึกษาในจังหวัดนครปฐม สังกัดสำนักงานเขตพื้นที่การศึกษามัธยมศึกษา เขต 9 โดยภาพรวม และรายด้านอยู่ในระดับมาก 3.การบริหารการวัดและประเมินผลการศึกษากับการปฏิบัติงานตามภารกิจการวัดและประเมินผลการเรียนรู้ ของสถานศึกษาในจังหวัดนครปฐม สังกัดสำนักงานเขตพื้นที่การศึกษามัธยมศึกษา เขต 9 มีความสัมพันธ์กัน อย่างมีนัยสำคัญทางสถิติที่ระดับ .01 THE EDUCATIONAL MEASUREMENT AND EVALUATION ADMINISTRATION AND THE PERFORMANCES OF ASSESSMENT MISSIONS ON STUDENT’S LEARNING OF SCHOOLS IN NAKHON PATHOM PROVINCE UNDER THE JURISDICTION OF THE SECONDARY EDUCATIONAL SERVICE AREA OFFICE 9 The purposes of this research were to determine 1) the educational measurement and evaluation administration of schools in Nakhon Pathom province under the Jurisdiction of the Secondary Educational Service Area Office 9 2) the performances of assessment missions on student’s learning of schools in Nakhon Pathom province under the Jurisdiction of the Secondary Educational Service Area Office 9 and 3) the relationships between educational measurement and evaluation administration and the performances of assessment missions on student’s learning of schools in Nakhon Pathom province under the Jurisdiction of the Secondary Educational Service Area Office 9. The samples were 28 schools in Nakhon Pathom province under the Jurisdiction of the Secondary Educational Service Area Office 9. The respondents were school administrators,school vice-administrators for academic affair or heads of academic affair , heads of learning department, a register of school, an evaluation teacher, as well as a teacher ; 6 persons per school, in total of 168 persons. The research instrument was a questionnaire regarding the educational measurement and evaluation administration of Kamol Puprasert et al. and the assessment missions on student’s learning performances of the Office of Basic Education Commission. The statistics used in data analyzing were frequency, percentage, arithmetic mean, standard deviation, and Pearson’s Product Moment Correlation Coefficient. The findings were as follows; 1.The educational measurement and evaluation administration of schools in Nakhon Pathom province under the Jurisdiction of the Secondary Educational Service Area Office 9, as a whole and as an individual aspect, was at a high level. 2. The performances of assessment missions on student’s learning of schools in Nakhon Pathom province under the Jurisdiction of Secondary Educational Service Area Office 9, as a whole and as an individual aspect, was at a high level. 3. There was the significant relationship between the educational measurement and evaluation administration and the performances of assessment missions on student’s learning of schools in Nakhon Pathom province under the Jurisdiction of the Secondary Educational Service Area Office 9 at .01 level of statistical significance.